2019
DOI: 10.22219/jrak.v9i3.9639
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Performance Measurement System for Lecturer (Pmsl): Comparison Among Three Models in Indonesia, Singapore and Turkey

Abstract: This study aims to explore the Performance Measurement System for Lecturer (PMSL) through a comparison study in three countries, namely Indonesia (MY), Singapore (IT), and Turkey (IMU). The comparative study is conducted by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…This result is in accordance with the results of previous studies which have revealed an increase in university performance after using an integrated computer-based application program [14]. The effectiveness of the program in improving performance because the system runs using applications according to the needs of the university [12].…”
Section: Results Of Feasibility Testsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is in accordance with the results of previous studies which have revealed an increase in university performance after using an integrated computer-based application program [14]. The effectiveness of the program in improving performance because the system runs using applications according to the needs of the university [12].…”
Section: Results Of Feasibility Testsupporting
confidence: 92%
“…Following the life cycle procedure, the results of the program compilation are analyzed by testing the system's performance. Multiple tests are conducted, including Stub Testing to verify the control structure of module performance mapping, Unit Testing to test the function of each module with Black Box Testing and White Box Testing, and Integration Testing to test interactions between modules, such as interface functions, user scenarios, data flow, and process flow [12]. The program is executed to pass the feasibility test if it already performs according to the program business that has been determined to meet users' particular needs.…”
Section: Methodsmentioning
confidence: 99%
“…Scopus and Web of Science are classified by the government as more reputable than Indonesian publication indexes (Irawan et al., 2018). Yet language barriers, as well as inadequate research funding and laboratory facilities make it difficult for many Indonesian scholars to gain access to highly ranked indexing platforms, such as Scopus, which does not index Indonesian‐language journals (Sofyani et al., 2019). Scholars who succeed in publishing in highly ranked international journals draw on public research funding to finance the cost of high APCs.…”
Section: Open Access and Research Qualitymentioning
confidence: 99%
“…Another study from Lee & Chiu (2022) describes an "Ask-Tell-Ask" feedback model that is effective in helping lecturers develop reflection and selfassessment skills, ultimately improving their performance. H. Sofyani et al (2019) compared lecturer performance measurement systems in three countries and found that aggressive and structured policies in Indonesia can significantly improve lecturer performance. Tattoo (2021) identified lecturer characteristics, course characteristics, and learning facilities as the main predictors of lecturer performance, explaining a 61.9% variation in lecturer performance.…”
Section: Introductionmentioning
confidence: 99%